Tinjauan Literatur: Evaluasi dan Keandalan Klasifikasi Massa Batuan Menggunakan Uji Beban Titik - Astika Putri Roshinta; Singgih Saptono; S. Koesnaryo; Tedy Agung Cahyadi; Eddy Winarno (Retii, 2020)
Rock mass classification is used as an important parameter in determining rock reaction to a construction, one of several rock mass classification methods is point load test. Point load test is preferred because of its ease in determining rock mass classes, both in terms of cost and time. Until now, many research results have been found that discuss the point load test with the aim of reducting the error value from the test result. In this research, a literature review was conducted from several research results to find outlines of things that must be considered and determine its superiority in converting to other test values. The results showed that the operator's ability, cone plate geometry, periodic tool maintenance, loading arm length and sample geometry as things to consider in point load test and point load index value can be converted to uniaxial compressive strength value, taking into account the geological conditions and correction values for each rock type.Keyword : PLT, rock mass classification, tool, test